Sterility Status of Reusable Medical Instruments at Public Hospital in Bandung - Rahayu, Hegandari S.; Kartidjo, Pudjiastuti (Pharmacology and Clinical Pharmacy Research)
Hospital-acquired infection has become serious issue during previous decades. In Indonesia, the prevalence of nosocomial infection reached almost 10% of total patients encounter. The objective of this study was to investigate the sterility status of 160 sets of re-used instruments in three intermediate care rooms, including High Care Cardiac Unit (HCCU), Neosurgical Critical Care Unit (NCCU) and Burn Care Unit (BCU) of Dr. Hasan Sadikin General Hospital and analyzed whether there was association between time and storage condition towards sterility status. All tested instruments were sterilized in Central Sterile Supply Department (CSSD) of the hospital and distributed to those intermediate care rooms. Observations and microbiology assays were carried out for four weeks. We found that the worst contamination was found in BCU room with 2.50% bacterial infection in week I, II and III, and 4.375% of fungal infection in week I, II and IV. The best sterility status of reusable instruments was found in CSSD, followed by NCCU, and HCCU. Time and storage condition influenced fungal contamination, while these factors did not associated with the bacterial contamination. In conclusion, sterility status of reusable medical instruments was relatively satisfactory, but there was still room for improvement, particularly at burn care facilities.Keywords: hospital-acquired infections, hospital, nosocomial, sterility